1990
DOI: 10.1038/clpt.1990.76
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and erythropoietic response to human recombinant erythropoietin in healthy men

Abstract: To assess the safety, pharmacokinetics, and erythropoietic responses to human recombinant erythropoietin (epoetin beta), single intravenous doses (10, 50, 150, and 500 IU/kg) were administered at monthly intervals to 16 healthy subjects in a two-panel, placebo-controlled, double-blind ascending-dose trial. A 1000 IU/kg dose was subsequently administered in an open manner. Epoetin concentrations were determined in serum and urine by radioimmunoassay. Reticulocyte, hemoglobin, and hematocrit values were serially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
52
3
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(66 citation statements)
references
References 0 publications
10
52
3
1
Order By: Relevance
“…When the degree of Epo induced by FG-2216 is compared with a standard dose of recombinant human erythropoietin (rHuEpo; at 100 U/kg of epoetin-␣ administered intravenously 3 times per week to dialysis patients), the peak Epo levels induced by FG-2216 are below that achieved by rHuEpo. 29,30 The increase of up to 37 g/L (3.7 g/dL) in Hb obtained with chronic dosing at the 60-mg/kg dose is consistent with the observed endogenous Epo induction. Additionally, chronic dosing protected against the development of anemia in animals undergoing weekly large-volume phlebotomy.…”
Section: Discussionsupporting
confidence: 59%
“…When the degree of Epo induced by FG-2216 is compared with a standard dose of recombinant human erythropoietin (rHuEpo; at 100 U/kg of epoetin-␣ administered intravenously 3 times per week to dialysis patients), the peak Epo levels induced by FG-2216 are below that achieved by rHuEpo. 29,30 The increase of up to 37 g/L (3.7 g/dL) in Hb obtained with chronic dosing at the 60-mg/kg dose is consistent with the observed endogenous Epo induction. Additionally, chronic dosing protected against the development of anemia in animals undergoing weekly large-volume phlebotomy.…”
Section: Discussionsupporting
confidence: 59%
“…EPO's nonlinear behavior has been documented in various animal species, including rats (Kato et al, 1997b), mice (Kato et al, 1998), rabbits (Yoon et al, 1997), sheep (Veng-Pedersen et al, 1999, and humans (Flaharty et al, 1990;VengPedersen et al, 1995VengPedersen et al, , 1999.…”
Section: Discussionmentioning
confidence: 99%
“…These data, which suggest a saturable process for EPO elimination, are consistent with clinical reports of EPO's nonlinear behavior. 15,33 In contrast, some studies have demonstrated, that the kidney and liver contribute to EPO elimination. [34][35][36] Urinary excretion has been shown to contribute in a minor way to EPO disposition with only approximately 5% of the administered dose excreted unchanged into the urine.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Instead, all received red blood cell transfusions that were administered to maintain Hb levels >12 g/dl for at least 24 h before a PK experiment, thereby avoiding the confounding effects of increased endogenous plasma EPO levels and perturbing EPO PK. 15,33 Assays Plasma r-HuEPO levels were measured in triplicate using a double-antibody radioimmunoassay. 49 Linear assay values for r-HuEPO concentrations are obtained between 4 and 62.5 mU/mL.…”
Section: Study Protocolmentioning
confidence: 99%